MANEJO DE DOENÇAS COM PRODUTOS ALTERNATIVOS ISOLADOS E ASSOCIADOS A FUNGICIDA NA CULTURA DA SOJA - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
The objective of this work was to evaluate the application of alternative products isolated and associated to fungicide in different sowing dates in the control efficiency of foliar diseases, physiological changes, defoliation, yield components, productivity and physiological quality of the seeds obtained in the soybean crop (Glycine max). Experiments were conducted in the field in Ponta Grossa, PR, Brazil, during the 2015/2016, 2016/2017 and 2017/2018 growing seasons with cultivars NA 5909 and TMG 7062. Treatments for the experiments were: 1-control (water) (V4, V6, R1 and R5.1), 2- Bacillus subtilis strain QST (V4, V6, R1 and R5.1), 3-Bacillus subtilis strain QST (V4 and V6) associated with azoxystrobin + benzovindiflupir (R1 and R5. 1), 4-chitosan 1% (V4, V6, R1 and R5.1), 5-chitosan 1% (V4 and V6) associated with azoxystrobin + benzovindiflupir (R1 and R5.1), 6-sulfur (V4, V6 , R1-R5.1), 7-sulfur (V4 and V6) associated with fungicide (R1 and R5.1), 8-sodium hypochlorite (V4, V6, R1 and R5.1), 9- sodium hypochlorite ( V4 and V6) associated with azoxystrobin + benzovindiflupir (R1 and R5.1), 10-azoxystrobin + benzovindiflupir (R1 and R5.1), 11-azoxystrobin + benzovindiflupir (V6, R1 and R5.1). In all treatments, Nimbus® adjuvant (0.5 v / v) was added. At the sowing in october the lowest disease severity occurred. The Asian rust area under the disease progress curve (AACPD) was lower in the cultivar TMG 7062, in the two sowing dates and growing seasons. In all growing seasons and sowing dates, alternative treatments with sulfur and chitosan (isolated), alternative treatments associated with fungicide and fungicide applied twice and three times, decreased the severity of Asian rust and powdery mildew in both cultivars. The fungicide increased the levels of chlorophyll α, β and total in cultivar TMG 7062. The cultivar TMG 7062 presented greater stomatal conductance, assimilation of CO2 and perspiration, in relation to NA 5909. The defoliation was reduced for both cultivars in the treatments with: sulfur isolated; the alternative products associated to the fungicide and the fungicide applied in two or three times, in all the seasons and sowing dates. The yield components affected were the number of pods per plant and the thousand grains weight. There was a reduction in productivity when the crop was sown in December. The cultivar TMG 7062 in the first sowing date did not respond to treatments for yield. The treatments with fungicide, sulfur, as well as the associated alternative products, prevented damages to productivity in all sowing dates, growing seasons and crops and cultivars. The sulfur treatment associated to the fungicide that was equivalent to the treatment with fungicide applied three times was highlighted, being possible the adaption of this management strategy by the producers of the region. Regarding the seeds obtained, the cultivar NA 5909 presented higher values of germination than the TMG 7062. The alternative products tested did not present phytotoxic effects to the seed germination of the two cultivars. In the second sowing dates there was a lower incidence of seed pathogens, which may justify the higher germination for both cultivars. The treatments that reduced the incidence of pathogens in the seeds were the isolated fungicide, B. subitilis and sulfur, isolated and associated to the fungicide in the two cultivars analyzed. There was no difference for the germination and sanity of the seeds submitted to two or three foliar applications of the fungicide.
Keywords: Glycine max; Phakopsora pachyrhizi; Microsphaera diffusa; Bacillus subtilis; Quitosana; hipoclorito de sódio; Produtividade; Glycine max; Phakopsora pachyrhizi; Microsphaera diffusa; Bacillus subtilis; Chitosan; Sodium hypochlorite; Productivity; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA